Hydraulic Conductivity of Organoclay and Organoclay-Sand Mixtures to Fuels and Organic Liquids - Benson, Craig H. (2015)
Hydraulic conductivity, swelling, and liquid sorption capacity (i.e., maximum organic liquid mass bound per mass organoclay solid) were measured for an organoclay with dimethylammonium bound to the surface. Five fuels (No. 1 fuel oil, No. 2 fuel oil, diesel, jet fuel, and gasoline), four pure organic liquids (methanol, phenol, ethylbenzene, and dioctyl phthalate), ranging from hydrophilic to hydrophobic, and Type II deionized (DI) water were used as liquids for solvation and permeation. The more hydrophilic liquids (methanol and phenol) and DI water resulted in low swelling (≤6 mL/2 g≤6 mL/2 g) or liquid sorption capacity (≤202%≤202%) and high hydraulic conductivity (>10−6 m/s>10−6 m/s). The term hydraulic herein refers to liquid and applies to all permeant liquids used. The less-refined fuels composed of heavier distillates (fuel oil and diesel) and the phthalate resulted in low swelling (10–12 mL/2 g10–12 mL/2 g) and liquid sorption capacity (<235%<235%) and intermediate to low hydraulic conductivity (10−10 to 10−11 m/s10−10 to 10−11 m/s). The highly refined fuels composed of lighter distillates and ethylbenzene resulted in higher swelling (>20 mL/2 g>20 mL/2 g), high liquid sorption capacity (<340%<340%), and very low hydraulic conductivity (typically, <10−11 m/s<10−11 m/s). The swelling, liquid sorption capacity, and hydraulic conductivity of this organoclay are related systematically; however, none of these properties correlates systematically with the common parameters describing hydrophobicity, namely, solubility or the octanol-water partition coefficient. When the swell index is at least 10 mL/2 g10 mL/2 g, this organoclay has hydraulic conductivity of less than 10−10 m/s10−10 m/s. Below 10 mL/2 g10 mL/2 g, the hydraulic conductivity increases rapidly as the swell index decreases. Sand-organoclay mixtures with uniform sand require more organoclay to achieve low hydraulic conductivity and are more sensitive to the swell index. For this organoclay, a mixture with at least 50% organoclay is recommended to ensure low hydraulic conductivity to gasoline and jet fuel. Diesel and fuel oil can require at least 75% of this organoclay to achieve low hydraulic conductivity.